Spider Systematics: Past and Future - Platnick, Norman I.; Raven, Robert J. (Zootaxa, 2013)
Spider systematics has a history that reaches back over 250 years, to the publication of Carl Clerck’s Svenska Spindlar (Clerck, 1757). Linnaeus (1758), in the famous 10th edition of his Systema Naturae that was published the following year (and which serves as the starting point for the rest of zoological nomenclature), recognized only 39 species of spiders, worldwide, even though he knew (and cited) Clerck’s book. Clerck had already recognized more species than that from Sweden alone, and (unlike Linnaeus) provided good, color illustrations of them, often including even drawings of the male palps. So it is not surprising that arachnologists take Clerck, rather than Linnaeus, as their starting point.